Spatiotemporal Evolution of Earthquakes in Longmenshan Fault and Adjacent Area, before and after the 2008 Wenchuan Earthquake - Gang Fan; Jun Wang; Shunchao Qi; Gongda Lu; Xingguo Yang; Jiawen Zhou (Shock and Vibration)
Seismicity sequence following a main earthquake usually contains much meaningful information for unveiling the focal mechanism and predicting the reoccurrence interval of large earthquakes. The spatiotemporal evolution of earthquakes before and after the 2008 Wenchuan earthquake (Ms 8.0) is analysed comprehensively in this study. The frequency-magnitude relation of the 3493 earthquake events retrieved from the database of the International Seismological Centre indicates that the adopted catalogue is complete for magnitudes ≥Ms 3.4. The seismicity during the 10 years before the Wenchuan earthquake remained stable, including the magnitudes and focal depths. However, seismicity attenuated sharply in the year following the Wenchuan earthquake, and the magnitude of earthquakes before the Wenchuan earthquake decreased gradually. The area of the seismogenic zone of the 2008 Wenchuan earthquake was smaller than the earthquake stricken area. The earthquakes that occurred in the Longmenshan fault area and adjacent area in the study period were mainly shallow earthquakes. The focal depths of earthquakes in the study area became stable gradually after the Wenchuan earthquake, mainly within the range from 10 to 16 km. The earthquakes in the study area were mainly distributed with an along-dip distance of 0–20 km, and the seismicity was distributed uniformly along the fault strike.